An Evaluation of a structured training event aimed at enhancing the Research Data Management Knowledge and Skills of Library and Information Science Professionals in South African Higher Education Institutions - Pienaar, Heila (University of Pretoria, 2016)
Mini Dissertation (MIT)--University of Pretoria, 2016.